ANALISA KEPUASAN MASYARAKAT ATAS KUALITAS PELAYANAN DI SUB –BAG HUMAS KEPOLISIAN RESORT SURAKARTA - Ari Pantjarani; Mursid Dwi Hastomo (STIE Atma Bhakti, 2019)
The fast competition in the present era of globalization is inevitably leading the value of public trust becomes increasingly important. In order for society to keep believing in an institution, the institution should meet the expectations of its customers. The fulfillment of customers’ expectations is marked with the customer’s satisfaction. By providing excellent service, it is expected that the society will increase their trust in the institution. This study aims to analyze the level of society’s satisfaction with the service quality of the Sub Division of Public Relations at the Surakarta Police Resort which focuses on studying the reliability, responsiveness, assurance, empathy, and tangible. The results showed that the dimensions of service quality provided by the Sub Division of Public Relations at the Surakarta Police Resort had been well marked with the results of the Service Quality (Servqual) concept where there was occurred a gap, namely the difference in reality and expectations.